A FEASIBILITY OF BUSINESS PORANG (Amorphophallus muelleri. Blum) IN EAST LOMBOK DISTRICT - Rini Endang Prasetyowati; Muhamad Sarlan; Dwi Haryati Ningsih (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
ABSTRACT Porang is a plant that lives in tropical forests. Plants that can also be grown in the lowlands are easy to live among forest tree stands, such as teak and sengon trees. Porang farming has promising prospects because it has economic value that can be developed. In addition, porang has many benefits, especially for industrial and health raw materials, this is due to the content of glucomannan substances contained in it. East Lombok Regency is one area that has great potential for the development of porang plants in West Nusa Tenggara Province. Porang farming is very potential for the community as an additional income for the community. However, with fluctuating market prices, porang farmers have concerns in implementing and developing porang farming. The purpose of this study was to examine the feasibility of porang farming in East Lombok Regency. Improvements in the cultivation system, technology and downstreaming of porang farming are expected to increase porang productivity which in turn increases farmers' income. Research activities are carried out in several stages, including: (i) site survey, identifying problems, and preparing proposals; (ii) data collection, data tabulation, and data analysis; (iii) draw conclusions and recommend the results of the study. The recommendations generated from this research are in the form of information related to the financial value obtained by porang farmers in East Lombok Regency. Based on the results of the study, it can be seen that the income obtained in porang farming is Rp. 39,696,316/LLG and Rp. 198.481. 580/hectare. And based on the calculation of the B/C ratio of porang farming in East Lombok Regency, the B/C ratio value 1 is 5.3. This shows that porang farming in East Lombok Regency is feasible.Keywords: Feasibility, Farming, Porang